On Multiple Functions of Translation: The Role of Translation in Diaspora, in Nation-Building and in Ideological Control. Interview with Nike Kocijančič Pokorn - Veličkienė, Deimantė (Vertimo studijos, 2022)
Interview with Nike Kocijančič Pokorn, University of Ljubljana
Keywords: -